2007
DOI: 10.1080/01496390701526612
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Aqueous Ionic Surfactant Solutions by Dynamic Ultrafiltration

Abstract: This paper investigates the reduction of concentration of an ionic surfactant (sodium dodecyl benzene sulfonate) present in an aqueous solution by ultrafiltration. A dynamic filtration system consisting of a metal disk rotating near a flat circular organic membrane was used in this study. Membranes cut off tested were 10, 20, and 50 kDa. The maximum rejection rate was 92% at 10 kDa. Permeate fluxes kept increasing with transmembrane pressure until at least 1400 kPa, reaching 400 Lh 21 m 22 at 10 kDa and 950 at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 18 publications
(21 reference statements)
0
3
0
Order By: Relevance
“…Due to the complex composition of industrial wastewater, simple solutions, emulsions and solid-liquid suspensions were preferred as test fluids. Simple solutions were used to mitigate toxic pollutants (halogenated organic compounds [39,40], 2-MIB and geosmin [41], polyvinyl alcohol [42], heavy metal ions [43,44] and sodium dodecylbenzene sulfonate [45,46]), artificial seawater (NaCl, KCl, MgCl2, CaCl2, and MgSO4) [47,48], viscous solutions (polyethylene glycol-6000 [49][50][51], carboxymethyl cellulose [52], ethanol [53]), soluble salts (CaSO4 [54], NaCl [55]), model wastewater in dairy process [56][57][58][59][60][61][62] and space mission [63]. For emulsion, oil/water mixtures with surfactants were considered [64][65][66][67][68][69][70].…”
Section: Water Treatmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to the complex composition of industrial wastewater, simple solutions, emulsions and solid-liquid suspensions were preferred as test fluids. Simple solutions were used to mitigate toxic pollutants (halogenated organic compounds [39,40], 2-MIB and geosmin [41], polyvinyl alcohol [42], heavy metal ions [43,44] and sodium dodecylbenzene sulfonate [45,46]), artificial seawater (NaCl, KCl, MgCl2, CaCl2, and MgSO4) [47,48], viscous solutions (polyethylene glycol-6000 [49][50][51], carboxymethyl cellulose [52], ethanol [53]), soluble salts (CaSO4 [54], NaCl [55]), model wastewater in dairy process [56][57][58][59][60][61][62] and space mission [63]. For emulsion, oil/water mixtures with surfactants were considered [64][65][66][67][68][69][70].…”
Section: Water Treatmentmentioning
confidence: 99%
“…However, it was opposite with specific energy consumption [65,135]. There were other studies focused on various test fluids [34,45,46,58,87,90,101,108,127,136,137,186,228], and were often compared to the other DF systems [19, 60, 66, 78, 88, 93, 94, 97-99, 104, 229].…”
Section: Rotating Diskmentioning
confidence: 99%
“…They found, during concentration tests, a logarithmic decay of flux with increasing concentration until reaching an oil concentration of 35%. The reduction of ionic surfactant (Sodium dodecyl benzene sulfonate) in aqueous solutions was investigated by Moulai-Mostefa et al (2007) using the UTC module and PES membranes, and they found that at lower pressure (900 kPa), no increase of flux was observed above 500 rpm, indicating that the flux was pressure limited, probably due to strong interactions between surfactant molecules. They observed that the flux reached a maximum at a certain speed depending upon inlet pressure, due to permeate back pressure.…”
Section: Mf and Uf Applicationsmentioning
confidence: 99%